Recent advances in dopamine D2 receptor ligands in the treatment of neuropsychiatric disorders - Juza, Radomir; Musilek, Kamil; Mezeiova, Eva; Soukup, Ondrej; Korabecny, Jan (Medicinal research reviews, 2023)
Dopamine is a biologically active amine synthesized in the central and peripheral nervous system. This biogenic monoamine acts by activating five types of dopamine receptors (D1-5 Rs), which belong to the G protein-coupled receptor family. Antagonists and partial agonists of D2 Rs are used to treat schizophrenia, Parkinson's disease, depression, and anxiety. The typical pharmacophore with high D2 R affinity comprises four main areas, namely aromatic moiety, cyclic amine, central linker and aromatic/heteroaromatic lipophilic fragment. From the literature reviewed herein, we can conclude that 4-(2,3-dichlorophenyl), 4-(2-methoxyphenyl)-, 4-(benzo[b]thiophen-4-yl)-1-substituted piperazine, and 4-(6-fluorobenzo[d]isoxazol-3-yl)piperidine moieties are critical for high D2 R affinity. Four to six atoms chains are optimal for D2 R affinity with 4-butoxyl as the most pronounced one. The bicyclic aromatic/heteroaromatic systems are most frequently occurring as lipophilic appendages to retain high D2 R affinity. In this review, we provide a thorough overview of the therapeutic potential of D2 R modulators in the treatment of the aforementioned disorders. In addition, this review summarizes current knowledge about these diseases, with a focus on the dopaminergic pathway underlying these pathologies. Major attention is paid to the structure, function, and pharmacology of novel D2 R ligands, which have been developed in the last decade (2010-2021), and belong to the 1,4-disubstituted aromatic cyclic amine group. Due to the abundance of data, allosteric D2 R ligands and D2 R modulators from patents are not discussed in this review.
Keywords: Ligands; Receptors, G-Protein-Coupled; dopamine D2 receptor; D2 receptor partial agonist; dopamin; Humans; ligandy; D2 receptor antagonist; anxiety; lidé; D2 receptor modulators; schizophrenia; receptory dopaminu D2; dopamine; Parkinson's disease; D2 receptor agonist; Dopamine; receptory spřažené s G-proteiny; depression; Receptors, Dopamine D2